The Presence of Microplastics in Shellfish: A Review - Aura, Selfi Monica; Deswati, Deswati; Emriadi, Emriadi (Universitas Pendidikan Mandalika, 2024)
This study aims to find the presence of microplastics in Shellfish through the literature review method of several studies conducted. The increase in plastic pollution in water systems since the 1950s has become a significant problem worldwide due to the slow decomposition rate. Microplastics, mainly primary and secondary, can accumulate in marine organisms such as Shellfish and enter the food chain, which is a concern for humans. Shellfish, especially M. galloprovincialis, can be used as bioindicators and bioremediation tools to tackle microplastic pollution. Microplastics are a severe problem in the world's oceans, especially in marginal and densely populated coastal areas. Marine organisms like Shellfish contain microplastics, which can cause physical damage and disrupt the immune system. Mytilus edulis clams and Crassostrea gigas oysters are the most consumed species with significant microplastic content. Research has also shown the presence of microplastics in Mytilus chilensis in the Gulf of Ushuaia, South America, with fibers and fragments being the most common types. Microplastics are also found in wild mussels in Tunisia, with the estimated annual dietary intake of microplastics by Tunisians through wild mussel consumption amounting to 4.2 particles per capita per year. Mussels of the genus Mytilus were proposed as guardian organisms to monitor microplastic pollution.